La plaisance à voile, fenêtre sur le paysage marin - Philippe Bodénan; Sébastien Coupez (Projets de Paysage)
The notion of seascape is seldom referred to in the scientific literature. Establishing links with the seascape in the same manner as the landscape has been approached in terrestrial spaces is not self-evident, as the usual reference points are disrupted. This work proposes to determine a number of milestones by studying the relationship established with the seascape by the practice of sailing. The article addresses the specific challenges posed by the seascape. But above all, it highlights aspects such as the reference points relating to this biophysical environment which make it possible for one to situate and orient oneself, the necessary adaptations for life at sea, and the representations conveyed by the practice of sailing.